0346 Occupational Exposure to Lead and Cancer in Two Cohort Studies of Men and Women in Shanghai, China. (23rd June 2014) - Liao, Linda M; Friesen, Melissa C; Xiang, Yong-Bing; Cai, Hui; Koh, Dong-Hee; Ji, Bu-Tian; Yang, Gong; Li, Hong-Lan; Locke, Sarah J; Rothman, Nathaniel; Zheng, Wei; Gao, Yu-Tang; et al.
Abstract : Objectives: Epidemiologic studies of occupational lead exposure have suggested increased risks of cancers of the brain, kidney, lung, meninges, and stomach; however, the totality of the evidence is inconsistent. To clarify whether lead is a carcinogen, we investigated the relationship between occupational lead exposure and risks of these five cancer sites in two prospective cohort studies in Shanghai, China. Method: Annual job/industry-specific estimates of lead fume and lead dust exposure were derived from a statistical model that combined expert ratings of lead intensity with inspection measurements collected by the Shanghai Centre for Disease Control and Prevention. The job/industry estimates were applied to the lifetime work histories of subjects from the Shanghai Women's Health Study (73 363 participants) and the Shanghai Men's Health Study (61 379 participants) to estimate cumulative exposure to lead dust and lead fume. Cohort-specific relative hazard rate ratios (RRs) and 95% confidence intervals (CI) were estimated using Cox proportional hazards regression models and then pooled using a random effects meta-analysis model. Results: We observed a statistically significant increased risk of meningioma among individuals with estimated occupational exposure to lead dust or fumes (RR=2.4, 95% CI:1.1–5.0), and in particular among those with an above-median cumulative exposure to dust or fumes (RR=3.1, 95% CI:1.3–7.4). We observed suggestive associations with lead exposure for cancers of the kidney (RR=1.4, 95% CI:0.9–2.3) and brain (RR=1.8, 95% CI:0.7–4.8), and null findings for cancers of the lung and stomach. Conclusions: Our findings provide additional evidence that occupational lead exposure increases risk of meningioma.